Fintech di Kota Pekalongan: Ketika Tradisi dan Teknologi Berkolaborasi - Putra, Mirsya (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2025)
Pekalongan City, as the center of batik culture, faces great challenges in integrating tradition with modern technology to support the sustainability of Micro, Small, and Medium Enterprises (MSMEs). Low access to formal financial services and digital literacy are major obstacles in improving the competitiveness of MSMEs in the digital era. This study aims to analyze the application of financial technology (fintech) among MSMEs in Pekalongan, identify challenges faced, and provide recommendations for strategic solutions. This research uses a qualitative approach with thematic analysis, data collected from various relevant secondary sources. The results show that fintech provides significant benefits, such as easing access to financial services, improving financial management efficiency, expanding market competitiveness, and encouraging product innovation. However, challenges include low digital literacy, limited internet infrastructure, and doubts about the security of digital transactions. Key recommendations include education and training for MSME players, strengthening digital infrastructure, and partnerships between the government and fintech providers. Collaboration between fintech and tradition has proven to be an effective synergy, not only in driving digital transformation but also maintaining local cultural identity. Keywords: Fintech, MSMEs, Pekalongan City, financial inclusion.